Association between the mean platelet volume-to-platelet count ratio and neurological outcomes in patients with out-of-hospital cardiac arrest - Lee, Ji Ho; Kim, Dong Ki; Ko, Sang Won; Lee, Dong Hun; Lee, Byung Kook (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effect of platelet activity on neurological outcomes in patients experiencing cardiac arrest. Method: The prospective, observational study was conducted from January 1 to December 31, 2023, after approval from the ethics review board of Chonnam National University Hospital, Gwang-ju, South Korea, and comprised patients of either gender aged >18 years who had out-of-hospital cardiac arrest. Serial mean platelet volume, platelet count, and mean platelet volume-to-platelet count ratio were noted at admission and on days 1, 2 and 3 after the return of spontaneous circulation. The primary endpoint was neurological outcome at 3 months. A poor neurological outcome was defined as cerebral performance categories 3, 4 and 5, while categories 1 and 2 were taken as a good neurological outcome. Data was analysed using SPSS 18. Results: Of the 86 patients with median age 62.0 years (interquartile range: 51.8-70.0 years), 61(75.5%) were males. Overall, 57(66.3%) patients had suffered cardiac arrest, while 30(34.9%) had shockable rhythms at sudden collapse. The median time between collapse and return of spontaneous circulation was 32.5 min (interquartile range: 21.8-44.0 minutes). Of the total, 62(72.1%) patients had a poor neurological outcome. The mean platelet volume-to-platelet count ratio at day 3 (adjusted odds ratio: 0.789; 95% confidence interval: 0.655-0.951; p=0.013) was independently associated with poor neurological outcomes. Conclusion: After return of spontaneous circulation, the mean platelet volume-to-platelet count ratio at day 3 may be a useful element for assessing the neurological outcomes in patients who having suffered out-of-hospital cardiac arrest and undergone targeted temperature management. Key Words: Mean platelet volume, Platelet count, Out-of-hospital cardiac arrest, Targeted temperature management.